2019
DOI: 10.20944/preprints201912.0316.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Past, Present and Future Perspectives on Groundnut Breeding in Burkina Faso

Abstract: Groundnut (Arachis hypogaea L.) is a major food and cash crop in Burkina Faso. Due to growing demand for raw oilseeds, there is an increasing interest in groundnut production from traditional rain-fed areas to irrigated environments. However, despite implementation of many initiatives in the past to increase groundnut productivity and production, the groundnut industry still struggles to prosper, due to several constraints including minimal development research and fluctuating markets. Yield penalty due to dro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 102 publications
0
12
0
Order By: Relevance
“…Formerly considered as a cash crop because of oil extraction, varieties with small seed were promoted because of their high oil content and are then the most available groundnut varieties disseminated in Burkina. The low productivity of groundnut observed in the study area is attributed to diverse production constraints (9,43). Although similar these constraints are ranked differently from one region to another.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Formerly considered as a cash crop because of oil extraction, varieties with small seed were promoted because of their high oil content and are then the most available groundnut varieties disseminated in Burkina. The low productivity of groundnut observed in the study area is attributed to diverse production constraints (9,43). Although similar these constraints are ranked differently from one region to another.…”
Section: Discussionmentioning
confidence: 98%
“…The present study revealed a subsistence groundnut farming system dominated by smallholder farmers in Burkina Faso. The cropping is characterized by extensive and low external input with big diversity across regions (9), largely depending on the rainfall which follow a north-south gradient, soil types and socio-economic conditions (2,27). The maturity cycle of groundnut varieties and cultural practices varied from one region to another region depending on rainfall distribution and soil typology (28).…”
Section: Discussionmentioning
confidence: 99%
“…Groundnut cropping is characterized by extensive and low external input with significant variability in production practices across regions, largely depending on the rainfall which follows a north-south gradient, soil types, and socio-economic conditions. Farming systems in west Africa and especially in Burkina Faso were characterized by huge variability from one region to another with poor technology and low investments [2,24,25] including the groundnut production system [2,9]. Nikiema [26] reported a varying onset of rainfall for the different agro-climatic zones in Burkina Faso.…”
Section: The Groundnut Cropping Systemmentioning
confidence: 99%
“…The national groundnut breeding program at the Institut National de l'Environnement et de Recherche Agricole (INERA) remained less organized to develop improved varieties that mitigate the constraints, and hence, it had little success in improving and disseminating new high-yielding varieties. The breeding activities were limited to varietal tests of elite materials from the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) [9]. The availability of improved variety seeds and policy support remained among the challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation